Embracing mountain microbiome and ecosystem functions under global change. Issue 6 (23rd March 2022) - Wang, Jianjun; Hu, Ang; Meng, Fanfan; Zhao, Wenqian; Yang, Yunfeng; Soininen, Janne; Shen, Ji; Zhou, Jizhong
Summary: Mountains are pivotal to maintaining habitat heterogeneity, global biodiversity, ecosystem functions and services to humans. They have provided classic model natural systems for plant and animal diversity gradient studies for over 250 years. In the recent decade, the exploration of microorganisms on mountainsides has also achieved substantial progress. Here, we review the literature on microbial diversity across taxonomic groups and ecosystem types on global mountains. Microbial community shows climatic zonation with orderly successions along elevational gradients, which are largely consistent with traditional climatic hypotheses. However, elevational patterns are complicated for species richness without general rules in terrestrial and aquatic environments and are driven mainly by deterministic processes caused by abiotic and biotic factors. We see a major shift from documenting patterns of biodiversity towards identifying the mechanisms that shape microbial biogeographical patterns and how these patterns vary under global change by the inclusion of novel ecological theories, frameworks and approaches. We thus propose key questions and cutting‐edge perspectives to advance future research in mountain microbial biogeography by focusing on biodiversity hypotheses, incorporating meta‐ecosystem framework and novel key drivers, adapting recently developed approaches in trait‐based ecology and manipulative field experiments, disentangling biodiversity–ecosystem functioning relationships and finally modelling and predicting their global change responses.